Interpretation of Values in the Epitaphs on the Tombstones of Old Jewish Cemetery in Bratislava - Jarmila Jurova; Marek Debnar (Communications - Scientific letters of the University of Zilina, 2018)
The aim of the paper is to find the most frequent links and connotations of the notions related to the values of the Jewish religious community in Bratislava before WWII. We understand community as an entity that requires adherence to a set of values, norms, and meanings; religious community is understood as one of the most important and influential constitutive communities in human life. We have therefore decided to process and analyse selected concepts and their closest semantic determinations in the corpus of epitaphs which were found on the tombstones of the Old Jewish Cemetery (already largely destroyed) in Bratislava. The research will be realized via advanced text analysis instruments and new IT tools which are gradually being introduced in wider research of humanities. Based on the research results, we will try to identify the basic values within this community and determine its interpretative traditions.